Do IPO Firms Become Myopic? - Maksimovic, Vojislav; Phillips, Gordon; Yang, Liu (Review of Finance, 2023)
Abstract We compare the growth and responsiveness to demand shocks of post-initial public offering (IPO) firms and their private counterparts. Using multiple measures of myopia and multiple ways to match IPO firms with private firms, we do not find evidence of myopic behavior by public firms. IPO firms respond more to investment opportunities and have higher productivity in their early public years. Our results on public firms’ sensitivity to growth opportunities hold under several robustness tests, including when we consider firms’ total growth including acquisitions. The results show the importance of matching public to private firms early in their life.